Comparative study on industrial air quality (Palm Oil Refinery) and lung function performance to receptor population in Banting, Selangor / Noradila Mohamed - Mohamed, Noradila (2011)
Background: A palm oil refinery factory located <500 meter from the residential area caused some problems to surrounding residents, especially related to air pollution. Arising of industrial development at Banting area especially focused to palm oil refinery factory contribute to cumulative air pollutants concentration to surrounding environment. The effectiveness of environmental management system (ISO 14001) implementation at factory is important to reduce air pollution problem. Study conducted to measure ambient air quality and health risk arising from the existence potential hazards.Methods: The level of air pollutants (PM10, SO2, NO2 and CO) concentration have been measured using EVM7 (Quest) at seven locations (n = 7), to identify the level of ambient air quality at the area. Lung function test also have been done to 90 respondents (n = 90) using Spirometer (Vitalograph) to identify their lung performance status (FVC, FEV1, FEV1/FVC). Questionnaires were given to the respondents to do surveillance regarding on the air